Aging as a risk factor for neurodegenerative diseases: insights from Ukraine and the world - Luhovyi, Oles; Bayliak, Maria (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2024)
Aging, often referred to as the autumn of life, is a natural and complex biological process that leads to a progressive decline in physiological functions, increasing susceptibility to various diseases, including neurodegenerative disorders. The neurodegenerative conditions, characterized by the loss of neuronal function and structure, include Alzheimer's disease (AD), Parkinson's disease (PD), and other dementias, which are leading causes of disability and mortality globally, particularly in the elderly. This article explores the most common theories of aging, relationship between aging and neurodegenerative diseases, and molecular and cellular processes underlying neurodegeneration. In particular, we discuss such theories of aging as epigenetic, damage and repair, and metabolic ones, as well as their importance for understanding neurodegenerative processes. At the cellular level, factors such as protein misfolding, mitochondrial dysfunction, and chronic inflammation link aging to neurodegeneration. Using statistical data, we examined the prevalence and mortality associated with these diseases in Ukraine, comparing trends with other countries. In particular, we examined the prevalence and mortality associated with neurodegenerative diseases over the past two decades in Ukraine, in two age groups: 50–69 years and 70+. Comparisons of data from Ukraine with global trends revealed that individuals aged 70+ experience a fourfold higher disease burden, as measured by disability-adjusted life years (DALYs). However, Ukraine demonstrates relatively low mortality rates for these diseases that may reflect underdiagnosis, shorter life expectancy, and unique demographic and socioeconomic factors. The findings emphasize the critical need for improved diagnostics, access to medical care, and population-based prevention strategies to address this growing health burden. Recommendations include early interventions targeting modifiable risk factors, increased research investment into age-related diseases, and the development of robust support systems for elderly populations. These efforts could significantly improve health outcomes, reduce healthcare costs, and enhance quality of life for aging populations.